الرشاقة وعلاقتها بمهارتين الطبطبة العالية والطبطبة بتغيير الاتجاه في كرة السلة لطلاب المرحلة الثانية - Bassem Juma Kazim; fadhil tariq amin; Abbas Abdul-kadhim Jabbar (Mustansiriyah Journal of Sports Science, 2021)
Research Summary The research was conducted to find out the relationship of agility with the skills of the high and the good, by changing the direction of the basketball for the second stage students, and the researcher used the descriptive approach to suit the nature of the study. On the research sample and the use of appropriate statistical means, through which the results of the research were reached, which confirm the existence of a moral correlation between agility and the skillful performance of the high and polite skills by changing the direction of basketball. Better